Percutaneous radiofrequency ablation of hepatocellular carcinoma in cirrhosis: analysis of complications in a single centre over 20 years - Giorgio, Antonio (Br J Radiol, 2017)
OBJECTIVE: To report on our 20 years' experience on complications after radiofrequency ablation (RFA) of hepatocellular carcinoma (HCC) in patients with cirrhosis. METHODS: From 1994 to 2014, 1787 RFA procedures were performed percutaneously in 1162 patients with cirrhosis (852 Child A and 310 Child B) with HCC nodules (1.2–7 cm), prothrombin time >50%, platelet count of 50.000 mm(3) and total bilirubin ranging from 0.80 to 4.5 mg dl(−1). In 67 patients, RFA was performed on both intraparenchymal HCC nodule and tumour thrombus extended in the main portal vein and/or its branches. RESULTS: Four patients (0.3%) died after RFA. 39 patients (3.2%) changed in Child's class: 26 out of 28 Child A patients with cirrhosis changed to Child B and 2 changed to Child C class; 11 Child B patients changed to Child C class. On multivariate analysis, the total bilirubin pre-RFA was the only independent risk factor for impairment of liver function and death. Complications were hemoperitoneum, abscess and intrahepatic haematoma. CONCLUSION: RFA of HCC in patients with cirrhosis is safe, even in case of invasion of the portal venous system. Functional liver reserve should be strictly monitored, mainly when pre-RFA total bilirubin value is >2.5 mg dl(−1). The study was approved by our institutional review board. ADVANCES IN KNOWLEDGE: The total bilirubin value >2.5 mg dl(−1) represents the main marker of functional liver reserve that predicts decompensation of liver cirrhosis in patients undergoing RFA for HCC.